Isolation and Characterization of E. coli Bacteriophage from Raw Meat and Environment Water - Islam, Mahbuba; Siddik, Md Abu Bakar; Mondol, Sudorshon; Hossain, Md Shahriar (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.